Model of Utilization Knowledge Management System Application - Fitriasari, Novi Sofia; Arifin, Willdan Aprizal (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The Knowledge Management System Application is an application that users can use to store and manage knowledge from the Community Of Practice (CoP) Marine Information Systems Study Program (SIK). CoP, known as the Expertise Group or KBK, consists of students and lecturers. The problem that exists based on the results of observations is that the Knowledge Management System Application called Asmape.Com application has not been utilized optimally; this can be seen from the use of the application, which is only used by three courses in the Marine Information Systems study program, namely knowledge management, business intelligence, and biodiversity. The successful implementation of an application depends on technological aspects and requires comprehensive attention to the existing dimensions of the information system. Therefore, it is necessary to model the utilization of knowledge management system applications (Asmape.com), which can be used as a systematic guide to understanding, analyzing, and improving performance. The methodology used is the information systems methodology from Hevner. One of the stages in the method is to determine the components using the Kitchenham systematic literature review. The study results show four layers in the model of utilizing knowledge management system applications: Infrastructure, Technology, Process, and Performance. The infrastructure consists of learning outcomes and technical skills components, and processes consist of Organization, People, Asmape Services, and Artifact Knowledge components. The performance consists of Pedagogic excellence, Digitalization Knowledge Management, and Openness Excellence.